ANALYSIS OF REPAIR WELDING ON BOILER TUBES DURING CONSTRUCTION BASED ON MECHANICAL PROPERTIES AND METALLOGRAPHIC ANALYSIS - Arief Wicaksana, Rizki
This study aims to analyze the repair welding conducted on a joint through tensile test, hardness test, and metallography. The study was performed on the main components of a boiler in a steam power plant (PLTU), which consists of a collection of tubes assembled using welding processes. During the welding application, defects were discovered through visual and radiographic examination methods, necessitating repeated repairs at certain welding points. In several projects, tubing spare parts were not accommodated in the contract documents, resulting in prolonged procurement processes when replacement was required. International standards do not regulate the number of times repair welding is allowed at a single joint, leaving uncertainty about how many repair welds can be performed on a weld joint. Therefore, this research aims to determine the permissible number of repair welds that can be performed on a joint. This study includes the initial weld joint, as well as three successive repair welding processes at the same point. The testing parameters include mechanical properties such as tensile strength, yield strength, elongation, and hardness, which are obtained through tensile and hardness tests. In addition, microstructural and macrostructural analyses of the metal were conducted using metallographic methods. The results of this research are expected to provide useful information for boiler construction, particularly in terms of repair welding on tubing that can be performed before replacing the tubing, thereby saving time and costs in procuring new materials. This study is also expected to provide a better understanding of repair welding's effects on the microstructure and mechanical properties of metallic materials.